(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Working capitalmanagement is an important aspect in firm’s financial management decision. Anoptimal working capital management is expected to contribute positively to thecreation of the firm value. To reach optimal working capital management firmmanager should control the tradeoff between profitability and liquidity judiciously.Main purpose of this study is to measure the liquidity position of the majorcomputers company and relationship between working capital and bank credit toknow managerial efficiency of working capital. For analyzing the data, ratioanalysis and various statistical tools and techniques were used. The data foranalysis covering the period (2008-2012) is collected from the financialstatements published in the annual reports. It was found that the position ofworking capital management of the company is very sound. It is also found thatthere is significant positive relationship between working capital and bankcredit.